Kegiatan Kedisiplinan Siswa di SMP Negeri 3 Leksono untuk Menerapkan Pendidikan Karakter - Ninik Tri Kusumadewi (Proceedings Series on Social Sciences & Humanities, 2023)
Through research that will be carried out on groups of class IX A students at SMP Negeri 3 Leksono, Wonosobo Regency, the aim is to describe the role of character education through disciplinary activities. This study uses qualitative research methods, the main instrument is the researcher himself. The data collection techniques used were interviews, observation, documentation and questionnaires. using the credibility test data validity test (internal validity). The credibility test is carried out by extending observations, increasing persistence in research, triangulation, discussions with colleagues, analysis of negative cases and member checks. The credibility test used is triangulation. This research was conducted at Leksono 3 Public Middle School, Wonosobo Regency from March to April 2022. The results of the study show that the disciplinary activities at SMP Negeri 3 Leksono to implement character education have been going quite well. This activity is carried out with disciplinary activities lining up outside the classroom before entering class to start learning, tadarus activities together, singing the Indonesia Raya song, every Friday there is Friday charity, midday prayers in congregation at the school prayer room. The method used to carry out these activities is the habituation method. Efforts to form the disciplined character of students in schools include everything that influences students to help them understand and adapt to environmental demands.